KELIMPAHAN BAKTERI COLIFORM PADA Cerithidea cingulata SEBAGAI INDIKATOR PENCEMAR DI PERAIRAN KAMAL KABUPATENBANGKALAN - Desi Rahmawati; Apri Arisandi (Juvenil, 2020)
ABSTRACTColifrom bacteria are a group of microorganisms commonly used as indicators of water pollutants to determine whether water or waters have been contaminated by pathogenic bacteria or not. This study aims to determine the parameters of water quality in Kamal waters, to determine the presence of colifrom bacteria in Kamal waters and to determine the abundance of colifrom bacteria. The sample used in the study was Cerithidea cingulata. Sampling was carried out in 3 location points, each of which had 5 plots for taking Cerithidea cingulata. Analysis of colifrom bacteria was carried out in three stages, namely the estimation test, confirmation test and colifrom MPN calculation. Based on the National Standardization Agency and SNI 7388: 2009, the maximum limit of coliform MPN values is 3MPN / g. On the location of Kamal Poron Stone can be seen the abundance of bacteria in Cerithidea cingulata between 3-15 MPN / g. whereas at the East Port location, Kamal can be selected for bacterial abundance in Cerithidea cingulata. between 3.6 - 35 MPN/g. and at the Kamal Climb location can be seen the abundance of bacteria in Cerithidea cingulata. between 3 - 1100 MPN / g, it is suspected that Kamal waters exceed the quality standard, which is 3MPN / g.Keywords: Coliform bacteria, Cerithidea cingulata, Bioindicator, PollutionABSTRAKBakteri colifrom merupakan golongan mikroorganisme yang lazim digunakan sebagai indikator pencemar perairan untuk menentukan air atau perairan telah terkontaminasi oleh bakteri pathogen atau tidak. Penelitian ini bertujuan untuk mengetahui parameter kualitas air diperairan kamal, untuk mengetahui adanya bakteri colifrom pada perairan Kamal dan untuk mengetahui kelimpahan bakteri colifrom. Sampel yang digunakan pada penelitian yaitu Cerithidea cingulata.Pengambilan sampel dilakukan 3 titik lokasi, setiap titik lokasi terdapat 5 plot untuk pengambilan Cerithidea cingulata.Analisa bakteri colifrom dilakukan dengan tiga tahap yaitu uji pendugaan, uji konfirmasi dan perhitungan MPN colifrom. Berdasarkan Badan Standarisasi Nasional dan SNI 7388:2009 mengatakan bahwa batas maksimal nilai MPN coliform yaitu 3MPN/g. Pada lokasi Batu Poron Kamal dapat dilihat kelimpahan bakteri pada Cerithidea cingulataantara 3 – 15 MPN/g. Sedangkan pada lokasi Pelabuhan Timur Kamal dapat dilihan kelimpahan  bakteri pada Cerithidea cingulata.antara 3,6 – 35 MPN/g. dan pada lokasi Tanjungan Kamal dapat dilihat kelimpahan bakteri pada Cerithidea cingulata.antara 3 - 1100 MPN/g maka diduga perairan Kamal melebihi batas baku mutu yaitu 3MPN/g. Kata Kunci: Bakteri Coliform, Rhinoclavis sordidula, Bioindikator, Pencemaran